Assessing teachers' collaborative lesson planning practices: Instrument development and validation using the SECI knowledge-creation model. (June 2022) - Mendoza, Norman B.; Cheng, Eric C.K.; Yan, Zi
Abstract: Collaborative lesson planning (CLP) is a key component of teachers' professional development that responds to students' ever-increasing learning needs. This study aimed to develop and validate an instrument to evaluate teachers' CLP practices. Guided by the SECI (socialisation, externalisation, combination, and internalisation) knowledge-creation model of Nonaka and Takeuchi (1995), items assessing CLP practices were developed. To validate the CLP scale, we analysed data from 540 primary and secondary school teachers in Hong Kong. Exploratory factor analysis on a random half of the sample suggests a four-factor solution that supports the SECI model. A confirmatory factor analysis and multidimensional Rasch analysis on the remaining half of the sample confirmed the four-factor structure. Both analyses support the dimensionality of the four-factor model, rating scale effectiveness, and item fit statistics. The final version of the CLPS has 21 items that assess teachers' CLP practices under the four SECI processes. This instrument has practical value in assessing, monitoring, and promoting collaborative teaching practices in school. The study's limitations and implications are discussed. Highlights: Successful curriculum reform requires teachers' collaborative lesson planning. The SECI model is a holistic framework to analyse teacher collaboration. An instrument to evaluate teachers' collaborative lesson planning is validated.